Synergistic effect of westerly circulation and western North Pacific anticyclone on interannual variation of mid-spring rainfall in southeastern China - Wenxu Lu; Xiaodong Liu (PLoS ONE, 2025)
The spring rainfall in southeastern China (SEC) is a unique climatic phenomenon and has important impacts on local socio-economics. In this study, the climatological characteristics of the SEC mid-spring (mid-March to early May) rainfall and the causes of its interannual variations are systematically analyzed using precipitation observations from 1961 to 2022. The results show that the interannual variations of SEC rainfall are mainly influenced by the westerly circulation (WC) south of the Tibetan Plateau, the western North Pacific anomalous anticyclone (WNPAC), and their synergistic effects. The WC is modulated by the mid-latitude Eurasian atmospheric wave train (AWT) and the thermal effects of the Tibetan Plateau. When the AWT is in a positive (negative) phase or the Tibetan Plateau experiences a cold (warm) spring, the WC and the bypassing flow on the plateau’s southeastern side strengthen (weaken), leading to excessive (deficient) SEC rainfall. During El Niño (La Niña) events in winter or spring, the warmer (cooler) tropical eastern Pacific forces Rossby waves to propagate westward, triggering an anomalous anticyclone (cyclone) in the northwest Pacific. This intensifies (weakens) the southwesterly flow on its western flank, ultimately enhancing (suppressing) SEC rainfall. More importantly, when these factors simultaneously exhibit simultaneous anomalous signals, the synergistic effect of the WC and WNPAC may become a key factor in forming extreme events of mid-spring rainfall in the SEC. This study helps deepen our understanding of the regional rainfall variation mechanisms and has the potential to be applied to short-term climate prediction.